Fenomena Gaya Berpacaran pada Dewasa - Rossy Autora Novithasari (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The role of teenagers in the world of dating today is very large, where teenagers have a tendency to have a high desire to build relationships between both parties. This research uses qualitative research with interview data as a source, while the analysis is carried out descriptively to describe the phenomenon of dating styles in teenagers. The results of this research are that teenagers' knowledge of dating is very high, this knowledge is part of symbolic interactionism which is born from the role of technology, in the phenomenon of teenagers' dating styles can be influenced by social environmental factors which are increasingly guarded and influential, influencing negative characters to become more positive and educational. which is actually better because of the strong support from current teenage dating.